1978
DOI: 10.1002/1098-2337(1978)4:4<353::aid-ab2480040406>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in aggressive behaviour in various strains of mice

Abstract: Two nonalbino inbred (C57 BL/6 and C3H/He) and one albino strain (Swiss) of mice were compared for female aggression toward intruders: 1 in period of lactation, 2 in nonlactating state and (3) in nonlactating state but previously rubbed with urine of lactating females; and for male aggression toward familiar or unfamiliar opponents. The results showed that resident females of the C57 and Swiss strain vigorously attack lactating intruders introduced into their cages. This effect was mediated by urinary cues emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 15 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Another strain of mice (C57 BL/6) directed attacks against lactating but not against nonlactating females. In a subsequent study, Haug and Mandel (1978b) showed that odoriferous factors were implicated in that aggression-stimulating effect and that the olfactory factor (a urinary one) is produced by the lactating females of the 3 strains.…”
Section: Un Ivers It T Lou Is Past Eur St Ras Bourg Francementioning
confidence: 98%
“…Another strain of mice (C57 BL/6) directed attacks against lactating but not against nonlactating females. In a subsequent study, Haug and Mandel (1978b) showed that odoriferous factors were implicated in that aggression-stimulating effect and that the olfactory factor (a urinary one) is produced by the lactating females of the 3 strains.…”
Section: Un Ivers It T Lou Is Past Eur St Ras Bourg Francementioning
confidence: 98%
“…It is possible that there is natural selection for some genes in males to respond more quickly and strongly to environmental pressures than females. In fact, Haug and Mandel (1978) found in mice that the aggression of the two sexes was under separate genetic or hormonal control Singh et al (1984) reported that even in monkeys, the behavioural responses to harsh and hostile environments are more marked in males, even to the extent of resulting in a higher male mortality as compared to females. …”
Section: Aggressive Dominancementioning
confidence: 99%